KASUS PELECEHAN SEKSUAL ANAK SEORANG PEJABAT TERHADAP SEORANG KORBAN YANG DIJADIKAN TERSANGKA DI PADANGSIDIMPUAN: KRITIK TERHADAP IMPLEMENTASI “UU NO. 25/2009” - Liardo, Yogi Rananta; Yusuf, M.; Yudanata, Agung; Aulia, Puja; Fadil Alfarizi, Muhammad; Azhara, Pinkkan; Pohan, Nur Habibah; Shafa, Fakhri (Gapenas Publisher, 2025)
Cases of sexual harassment often occur in Indonesia, one of which is the case of the son of an official in Padangsidimpuan which led to the criminalization of the victim becoming a suspect, revealing serious problems in the implementation of the law in Indonesia, especially related to the protection of victims of sexual harassment. That victimization can indeed occur when there is a loophole committed by the victim, but still the victim needs to be given legal protection so that the rights owned by the victim are fulfilled. This study criticizes the implementation of Law No. 25 of 2009 concerning Public Service, which regulates the right to fair and transparent public service and analyzes the factors that cause the criminalization of victims, including social stigma, impartial legal approaches, and lack of understanding of the dynamics of sexual violence. The research method used in this article is the Literature study method where the data obtained by the researcher will then be analyzed and data validity will be carried out. The results of this study show that victim criminalization can indeed occur, but if the party committing the criminalization has enough evidence to commit the crime, but still must pay attention to the excuse and justification reasons owned by the victim. Criticism of the implementation of this law is expected that in carrying out public services, government officials do not abuse their authority to other communities.